AI-Driven Intelligent Chatbots for Conversational English Practice: A Solution for Speaking Anxiety in Pakistani Students - Khaliq, Dr. Abdul; Haroon, Muhammad; Sajid, Muhammad Wahaj (ACADEMIA International Journal for Social Sciences, 2026)
Speaking anxiety is still a major obstacle to effective learning of English language among Pakistani ESL learners which tend to inhibit participation, confidence as well as fluency in oral communication. This paper examines the application of AI-based intelligent chatbots as a pedagogical tool to help reduce speaking anxiety and improve conversational English proficiency. Using a quantitative research design, the data were gathered with 200 university students with the questionnaire being structured in a Likert-scale with the data being analyzed using SPSS applying the descriptive statistics, correlation, regression and t-tests. The results indicate that the use of chatbots is strongly linked to the decreased anxiety related to speaking and the increased confidence and fluency, with frequent users showing better results as compared to occasional users. The chatbots were also seen as a safe, interactive, and non-judgmental space, which can be used to practice regularly and reduce psychological barriers to communication. But, constraints connected to the contextual knowledge and deficiency of emotional richness was identified. The paper concludes by stating that AI chatbots have the potential to become an effective auxiliary tool in ESL teaching, especially when it comes to dealing with affective issues. To be successfully integrated, pedagogical support, AI literacy and compatibility with traditional teaching methods are necessary to achieve meaningful and sustainable learning outcomes.